2020
DOI: 10.1007/s40200-020-00495-3
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of Lactobacillus casei derived extracellular vesicles on toll-like receptor 9 gene expression and cytokine profile in human intestinal epithelial cells

Abstract: Background A complex community of microorganisms in the gastrointestinal (GI) tract, known as the gut microbiota, exerts major effects on gene expression and cytokine profile. Extracellular vesicles (EVs) which are produced by bacteria could be sensed by Toll like receptors (TLRs). The interaction between gut microbiota and TLRs affects homeostasis and immune responses. In this study, we evaluated TLR9 gene expression and cytokines level in Caco-2 cell line treated with Lactobacillus casei as one of the gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…On the other hand, EVs from E. coli and L. casei increased NF-κB levels per se in Caco-2 and HT-29 cell lines ( Cañas et al, 2018 ; Bäuerl et al, 2020 ). This opposite modulation of NFκB levels, in the presence or absence of LPS, was also observed for pro-inflammatory cytokines like IL-8 in both Caco-2 and HT-29 cell lines, and in ex vivo human colonic explant ( Fábrega et al, 2016 ; Choi et al, 2020 ; Vargoorani et al, 2020 ).…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, EVs from E. coli and L. casei increased NF-κB levels per se in Caco-2 and HT-29 cell lines ( Cañas et al, 2018 ; Bäuerl et al, 2020 ). This opposite modulation of NFκB levels, in the presence or absence of LPS, was also observed for pro-inflammatory cytokines like IL-8 in both Caco-2 and HT-29 cell lines, and in ex vivo human colonic explant ( Fábrega et al, 2016 ; Choi et al, 2020 ; Vargoorani et al, 2020 ).…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 65%
“…In vitro and in vivo experiments with intestinal epithelial cells have demonstrated that EVs released by E. coli , L. casei , L. paracasei , P. freudenreichii , and L. rhamnosus can modulate NFκB levels ( Cañas et al, 2018 ; Bäuerl et al, 2020 ; Choi et al, 2020 ; Vargoorani et al, 2020 ; Tong et al, 2021 ). NF-κB is a family of transcription factors and has an essential role in a variety of aspects related with human health including the development of both innate and adaptive immunity.…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 99%
“…Dynamic light scattering (DLS) (9/60; 15%) was used less commonly for this purpose ( Figure 1 and Table S1 ). In 11 articles, more than one technique was applied to determine the size of EVs, including 6 with microscopy + NTA [ 29 , 30 , 31 , 32 , 33 , 34 ], 3 with microscopy + DLS [ 35 , 36 , 37 ], and 2 with microscopy + NTA + DLS [ 38 , 39 ] ( Figure 1 and Table S1 ). Among other parameters of EVs measured by researchers, the surface charge/zeta potential and the quantity of EVs can be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, the parameters of EVs other than dimensions—surface charge/zeta potential and quantity—are of little interest to scientists. In the studies in which this topic was addressed, the zeta potential of EVs had negative values between −0.5 mV [ 37 ] and −45 mV [ 42 ], with an average ranging from −10 mV to −20 mV ( Table S1 ). The phenomenon of negative charge of EVs is most often related to the presence of extracellular DNA on the surface of these structures, which translates into their important function in supporting adhesion, aggregation, and biofilm formation of microbes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might describe one potential mechanism of the role of dysbiosis [15,16]. MVs isolated from different strains of Bifidobacterium and Lactobacillus may mediate the probiotic impacts of the MV-releasing microbes [20]. Studies investigating the immunoregulatory roles of MVs have unraveled pro-and anti-inflammatory effects [21][22][23].…”
Section: Introductionmentioning
confidence: 99%